2020
DOI: 10.3390/ijerph17041437
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Teacher’s Prosocial Skills on the Mindwandering, Creative Intelligence, Emotions, and Academic Performance of Secondary Students in the Area of Physical Education Classes

Abstract: Physical Education classes are a key context for the development of creativity due to interactions with peers and the resolution of complex motor skills. Therefore, the aim of this study is to analyze the influence of the teacher's social behaviors on the mindwandering, emotional state, and academic performance of Physical Education students. The study involved 606 high school students and 36 physical education teachers. A structural equation model was used to analyze the relationship between the variables of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
(49 reference statements)
0
16
0
7
Order By: Relevance
“…In this sense, a study conducted by Lirola et al [ 51 ] in a population of adolescents showed how motivation towards PE classes has a positive influence on attitude, behavioral control and subjective norms, favoring healthy and balanced eating. In the same way, but with regard to the practice of physical activity, a study carried out in a population of adolescents by Trigueros et al [ 8 ] analyzed how motivation towards PE classes was positively related to attitude, behavioral control and subjective norms, and, in turn, attitude, behavioral control and subjective norms showed a positive relationship with regard to the intention to practice PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, a study conducted by Lirola et al [ 51 ] in a population of adolescents showed how motivation towards PE classes has a positive influence on attitude, behavioral control and subjective norms, favoring healthy and balanced eating. In the same way, but with regard to the practice of physical activity, a study carried out in a population of adolescents by Trigueros et al [ 8 ] analyzed how motivation towards PE classes was positively related to attitude, behavioral control and subjective norms, and, in turn, attitude, behavioral control and subjective norms showed a positive relationship with regard to the intention to practice PA.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, Physical Education (PE) classes can play a fundamental role in promoting healthy lifestyle habits, as their objectives include healthy and balanced nutrition and the adoption of active habits during leisure time [ 7 ]. In addition, the influence of parents and teachers on the dietary behaviour and physical exercise of young people is fundamental [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As emotions are elicited by situational facets of the learning environment and personal prerequisites (such as overall well-being) through cognitive appraisals, this can lead to a dangerous spiral with exhausted, unsatisfied teachers who experience even more negative emotions in class (Goetz et al, 2015). On the other side, teachers who manage their emotions effectively and report to have a balanced life, have students who experience greater social and emotional well-being (Braun et al, 2020), higher academic performance and creativity (Trigueros et al, 2020), among other benefits. Hence, it is important to explore the relations and interplay between teacher emotions and overall wellbeing in more depth and to also identify sources of teachers' well-being regarding work-related characteristics.…”
Section: Emotions and Well-beingmentioning
confidence: 99%
“…Peran pimpinan dalam melakukan intervensi menciptakan atmosfir yang kondusif dilakukan agar kinerja guru dan staf menjadi maksimal, misalnya pemahaman peserta didik, pembuatan rencana pembelajaran yang memfasilitasi perbedaan, dan melakukan evaluasi belajar dengan mengedepankan prinsip universal Berdasarkan analisis data, didapatkan bahwa hubungan budaya sekolah dan kinerja adalah signifikan dengan besar pengaruh sebesar 0.387 (38,7%). Guru yang memiliki sikap prososial berdampak positif kepada lembaga, misalnya dapat meningkatkan kreatifitas siswa, kecerdasan emosi, akademik (Trigueros, 2020) menjadikan kelas lebih menarik, meningkatkan keterlibatan siswa dalam pembelajaran, menguatkan pendidikan karakter (White & Shin, 2016), mengurangi konflik (Morengo el al. 2018) dan mempercepat pencapaian tujuan lembaga (Yana et al, 2020).…”
Section: Pendahuluanunclassified